Frame to Improve the Fit of N95 Filtering Face Mask Respirators. Issue 6 (June 2021) - Stemen, Daniel; Ge, Marshall; Hwang, Darryl; Qaddoumi, Burhan; Roden, Mark; Nanda, Neha; Ference, Elisabeth
Abstract : Objective: Test a device that can improve upon the seal of filtering face mask respirators (FFRs). Methods: A 3-D prototype for a fit improvement frame (FIF) was created and quantitative fit testing was performed for FFRs with and without the FIF. Results: Thirty eight volunteers underwent fit testing. The overall fit pass rate was 100% for the 3M model 1860 masks, 50% for the 3M model 8511 masks, 13% for the BYD CARE model DE2322, and 7% for the Honeywell DC300N95. When using the FIF the overall passing rate increase to 87% for the DE2322 + FIF ( P  < 0.01) and for the DC300N95 + FIF the passing rate increase to 73% ( P  < 0.01) Conclusion: The FIF is effective in improving the mask fit of a common flat fold N95 masks and potentially other N95 masks.